Implementasi Pengawasan Pemerintah Pusat Terhadap Peraturan Daerah Kabupaten Hulu Sungai Selatan - Lies Ariany (Fiat Justisia: Jurnal Ilmu Hukum, 2012)
Supervision is should be the central government to the Hulu Sungai Selatan associated with the implementation of government and especially to local regulations. The authority is possession the central government through the competent authorities to supervise the authorities of the Hulu Sungai Selatan in shaping legislation, because it can be understood that the independence of the implementation of autonomy does not mean the area can make laws or decisions regardless of system of national legislation. The local level legislation is an integral part of the unified system of national legislation. Therefore, the local level legislation must not contrary with the regulations of higher level and also to must not contrary to the public interest. Key words: Otonomi daerah, pengawasan, peraturan daerah